Resources in Earth Observation - CSIRO Office of Space Science & Applications (Canberra, Australia IbCSIRO, 1996)
Case Studies, Data and Information for Schools and Developing Countries Concerning Earth
Used Directly on a PC Running Windows 3.1 or 95
Keywords: Earth -- Software